Stereoselective formal total synthesis of novel antibiotic (-)-centrolobine - Mohapatra, Debendra K.; Pal, Rita; Rahaman, Hasibur; Gurjar, Mukund K. (Heterocycles, 2010)
A concise and stereoselective formal total synthesis of (-)-centrolobine is achieved utilizing Mioskowski's Lewis acid mediated epoxide opening followed by ring-closing metathesis as the key reaction.
Keywords: antibiotic; Centrolobine; Keck allylation; Ring-closing metathesis; Sharpless asymmetric epoxidation

Enantioselective synthesis of (+)-hygroline and (+)-pseudohygroline via Keck allylation and CBS reduction - Bhoite, Shubhangi P.; Kamble, Rohit B.; Suryavanshi, Gurunath M. (Tetrahedron Letters, 2015)
An enantioselective synthesis of (+)-hygroline and (+)-pseudohygroline has been achieved in high optical purity (98% ee) from readily available 1,4-butanediol. The synthesis strategy employs a Keck allylation, CBS reduction, and Wacker oxidation. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: CBS reduction; Keck allylation; Pyrrolidines; Wacker oxidation

Studies toward the total synthesis of (+)-neopeltolide using N-heterocyclic carbene-catalyzed oxo-acyloxylation/reductive oxa-Michael addition strategy - Reddi, Rambabu N.; Sudalai, Arumugam; Jo, Changbum (Bulletin of the Korean Chemical Society, 2022)
This article describes a concise synthesis of two important fragments (tetrahydropyran [THP] and ketone moieties) of the cytotoxic macrolide (+)-neopeltolide in 10 long linear steps in enantiomerically pure form. Asymmetric Keck allylation to install the required C11 and C13 stereocenters, N-heterocyclic carbene (NHC)-catalyzed oxoacyloxylation to functionalize alkenes, and reductive oxa-Michael addition to construct 2,6-difunctionalized THP unit intramolecularly are the important steps in synthetic efforts. Finally, Keck asymmetric allylation and Lewis acid-catalyzed diastereoselective allylation of the aldehyde were sequentially employed to establish the stereocenters at C11 and C13 positions, respectively.
Keywords: (+)-neopeltolide; Keck allylation; Macrolide; NHC-catalyzed oxoacyloxylation; reductive oxa-Michael addition